Kapasitas Lentur Balok Beton Tulangan Bambu Ori Takikan Jarak 20 dan 30 mm - Budi, Agus Setiya; Rismunarsi, Endang; Kharir, Kharir (Department of Civil Engineering, Diponegoro University, 2016)
Bamboo is one of the potential material as a substitute for steel reinforcement. This paper will discuss the flexural capacity of concrete beam with Ori bamboo reinforcement notch V type. The use of the notch is expected to minimize the effects of shrinkage and slip. This study uses laboratory experimental method. Bamboo is used at least 2.5 years old. Bamboo in a notch with a V-shape with the distance between the notch is 2 cm and 3 cm. The sample size used in the form of a concrete beam is 11x15x170 cm. The compressive strength of concrete (fc’) used was 18.3 MPa, yield strength of bamboo (fyb) with nodia is 276.56 MPa, and a yield strength of steel (fys) is 486.6 MPa. Static loading is done with third point loading system. For comparison also tested steel reinforcement concrete beam with Ø-8 mm. Based on test results, the average value of flexural capacity test on a sample of concrete beams reinforced bamboo Ori V notches on the distance between the notch 20 mm is 0.412 tm, and the average value of flexural capacity on the distance between the notch 30 mm is 0.387 tm and the average value of flexural capacity of concrete beam test with steel reinforcement Ø-8 mm is 0.516 tm.